Ethnocultural processes among the Chukchi in the 20th century - Diachkova, Galina (Études/Inuit/Studies, 2007)
AbstractThis paper briefly describes the Chukchi component of a research project entitled “The role of the community-based organisations of the North, Siberia and the Far-East in the Russian Federation’s social policies.” This study, initiated in 2001, focuses on the ethnocultural processes that impact on the development of the contemporaneous Chukchi community.